A Study to Access the Effect of Planned Teaching in Relation to a Selected Aspect of Pregnancy-Induced Hypertension among Antenatal Mothers at a Government Hospital Mumbai - Raosaheb Palve, Sujata (International Journal of Nursing Research, 2023)
Background: Hypertension is one of the common complications and contributes significantly to perinatal mortality and morbidity. Hypertension is a sign of underlying pathology which may be pre-existing or appear for the first time during pregnancy. The identification of the clinical entity and effective management plays a significant role in the outcome of pregnancy, both for the mother and the baby. Aim: The main aim of the study was to assess the effect of planned teaching on knowledge regarding pregnancy-induced hypertension (PIH) among antenatal mothers. Methods: The study was conducted on conveniently selected 30 samples of antenatal mothers in Government Hospital, Mumbai. The data collection process started from April 11, 2010, to May 2, 2010, after getting the required permission from the respective authorities. Data were collected by sociodemographic variables and self-structured knowledge questionnaire. Collected data were analyzed by descriptive and inferential statistics. Results: The study finds the results that the knowledge on the concept of hypertension, etiology and risk factors, signs and symptoms, investigations, exercise-related management of PIH, dietary management, prevention, and complications during PIH was significantly higher after teaching program in comparison to before teaching program. Overall knowledge of antenatal mothers to manage hypertension was significantly higher post-test in comparison to pre-test. Thus, results indicated that the planned teaching had a significant impact on knowledge regarding PIH among antenatal mothers. Conclusion: In this study, the post-test knowledge score was associated with education and occupation.